2018
DOI: 10.1002/smtd.201800048
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Graphene Oxide Electrodes with Wrinkled Surface for Nonvolatile Polymer Memory Device Compatibility

Abstract: A general strategy for high performance nonvolatile polymer memory devices, with wrinkled reduced graphene oxide (rGO) films as electrodes and common insulating polymers as active layers, is proposed. The fabricated device exhibits electrical bistability and nonvolatile write‐once‐read‐many times‐type memory, with a low switching voltage of 2.7 V, high ON/OFF ratio of 104 and desirable long retention time over 104 s. The resistive switching of the device might be attributed to carbon‐rich filaments induced by … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
22
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 39 publications
3
22
0
Order By: Relevance
“…[1][2][3][4] Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra-low power memory devices during their practical 3D integration. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously.…”
Section: Doi: 101002/aelm201800503supporting
confidence: 89%
See 1 more Smart Citation
“…[1][2][3][4] Building polymer memory devices with low resistive switching voltage hold great importance in their fundamental study as well as the technical advancement of ultra-low power memory devices during their practical 3D integration. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously. [7][8][9] However, most polymer memory devices remain at high resistive switching voltages in accordance to the research reported previously.…”
Section: Doi: 101002/aelm201800503supporting
confidence: 89%
“…(see details in Experimental Section). [9] After spin-coating Ag NPs onto the w-rGO electrodes, the surface roughness increases significantly, suggested by the 3D surface topography of the w-rGO@Ag NPs electrodes, indicative of the successful modification of Ag NPs onto the surface of w-rGO film. Finally, 180 nm top Al electrodes were deposited onto the polymer layer via thermal evaporation.…”
Section: Doi: 101002/aelm201800503mentioning
confidence: 97%
“…SiO 2 (300 nm)/Si substrates were purchased from SZJXTech (SuZhou, China). The rGO/SiO 2 (300 nm)/Si and patterned rGO/SiO 2 (300 nm)/Si substrates were prepared according to our previous studies …”
Section: Methodsmentioning
confidence: 99%
“…Since its discovery, graphene has undergone a rapid development and shown broad prospects in a variety of fields including batteries, sensors, field‐effect transistors, and optoelectronic devices 142‐150 . Notably, graphene‐based materials have also demonstrated as promising alternatives for resistive memory applications, thanks to its easy solution‐processing features, outstanding physical and chemical adjustability, 3D stacking capability, and possibility of obtaining heterostructures 51,151‐167 . The most common solution‐processing forms of graphene‐based derivatives for resistive memory are GO and rGO 51,154,156 .…”
Section: D Graphene‐based Materials For Resistive Memorymentioning
confidence: 99%